Mechanistic Diversity in the RuBisCO Superfamily: RuBisCO from Rhodospirillum rubrum is Not Promiscuous for Reactions Catalyzed by RuBisCO-Like Proteins (RLPs)() - Warlick, Benjamin P. E. (2012)
D-Ribulose 1,5-bisphosphate carboxylase/oxygenases (RuBisCOs) are promiscuous, catalyzing not only carboxylation and oxygenation of D-ribulose 1,5-bisphosphate but also other promiscuous, presumably nonphysiological, reactions initiated by abstraction of the 3-proton of D-ribulose 1,5-bisphosphate. Also, RuBisCO has homologues that do not catalyze carboxylation; these are designated RuBisCO-like proteins or RLPs. Members of the two families of RLPs catalyze reactions in the recycling of 5′-methylthioadenosine (MTA) generated by polyamine synthesis: 1) the 2,3-diketo-5-methylthiopentane 1-phosphate (DK-MTP 1-P) “enolase” reaction in the well-known “methionine salvage” pathway in species of Bacilli; and 2) the 5-methylthio-D-ribulose 1-phosphate (MTRu 1-P) 1,3-isomerase reaction in the recently discovered “MTA-isoprenoid shunt” that generates 1-deoxy-D-xylulose 5-phosphate (DXP) for nonmevalonate isoprene synthesis in Rhodospirillum rubrum. We first studied the structure and reactivity of DK-MTP 1-P which was reported to decompose rapidly [Ashida, H., Saito, Y., Kojima, C., and Yokota, A. (2008) Biosci Biotechnol Biochem 72, 959–67]. The 2-carbonyl group of DK-MTP 1-P is rapidly hydrated in solution and can undergo enolization both nonenzymatically and enzymatically via the small amount of unhydrated material that is present. We then examined the ability of RuBisCO from R. rubrum to catalyze both of the RLP-catalyzed reactions. Contrary to a previous report [Ashida, H., Saito, Y., Kojima, C., Kobayashi, K., Ogasawara, N., and Yokota, A. (2003) Science 302, 286–290], we were unable to confirm that this RuBisCO catalyzes the DK-MTP 1-P “enolase” reaction either in vitro or in vivo. We also determined that this RuBisCO does not catalyze the MTRu 1-P 1,3-isomerase reaction in vitro. Thus, although RuBisCOs can be functionally promiscuous, RuBisCO from R. rubrum is not promiscuous for either of the known RLP-catalyzed reactions.